2016
DOI: 10.5539/elt.v9n8p190
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation among EFL Learners’ Test Anxiety, Foreign Language Anxiety and Language Achievement

Abstract: The main aim of this study was to investigate the correlation among test anxiety (TA), foreign language anxiety (FLA) and language achievement of university preparatory students learning English as a foreign language. The sample of the research consisted of 301 (211 females, 90 males) attending a one-year EFL preparatory school at Ondokuz Mayıs University, School of Foreign Languages. The TAI (Test Anxiety Inventory) developed by Spielberger (1980), FLCAS (Foreign Language Classroom Anxiety Scale) developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…In another study of EFL context for Korean students, Poupore (2013) found that being anxious during language learning can make students reluctant to join activities in the class. The negative correlation between English oral test performance and anxiety are significant in other several studies (Cakici, 2016;Philips, 1992;Said & Weda, 2018;Teimori, Goetze, & Plonsky, 2019).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In another study of EFL context for Korean students, Poupore (2013) found that being anxious during language learning can make students reluctant to join activities in the class. The negative correlation between English oral test performance and anxiety are significant in other several studies (Cakici, 2016;Philips, 1992;Said & Weda, 2018;Teimori, Goetze, & Plonsky, 2019).…”
Section: Introductionmentioning
confidence: 56%
“…A questionnaire named FLCAS (Foreign Language Class Anxiety Scale), which was originally developed by Horwitz et al (1986) was administered to the participants. FLCAS have also been used to investigate the level of anxiety which further is correlated to language achievements (Cakici, 2016;Hewitt & Stephenson, 2017;Philips, 1992;Teimori et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is observed that researchers mostly focused on the relationship between foreign language anxiety-academic achievement and shyness-academic achievement. There are few studies with three or more independent variables (Bashosh et al, 2013 ;Chu, 2008;Cakici, 2016)…”
Section: Studies On Shyness Language Anxiety and Language Learning Smentioning
confidence: 99%
“…Self-esteem is assessed as a developmental phenomenon and varies in different periods of life and in light of different events (Lubow, 2009). Test anxiety has been shown to be one of these experiences (Ahangary & Sharifi, 2015;Dan, Bar Ilan, & Kurman, 2014;Dan & Raz, 2015). In the literature, positive experiences increase the individual's self-esteem, while it is clear that when faced with negative experiences or failures, self-esteem reduces (Mruk, 2006).…”
Section: Test Anxiety and Life Satisfactionmentioning
confidence: 99%